Aristotle on Ownership - Hennig, Boris (Phronesis, 2025)
I argue that despite certain appearances, Aristotle does not think of ownership as the exclusive right of a person to decide upon the use and alienation of a thing. Rather, in Aristotle, ownership is a relation between a person and a thing such that (1) the thing is instrumental for this person’s life, (2) it is external to the organic body of the person, and (3) the person is protected against being excluded from the relevant kinds of access to the thing.